HUBUNGAN PENGETAHUAN TENTANG PENGOBATAN PADA PASIEN DIABETES MELLITUS DENGAN TINGKAT KEPATUHAN PEMERIKSAAN RUTIN (Studi Analitik Di Poli Penyakit Dalam RSUD PareâKediri Tahun 2010) - Kosasih, Muhamad Ikhwan; Salafiah, Binti (Jurnal AKP, 2011)
Nowadays, the obedience of patient with diabetes mellitus due to the routine control are still being a problems. Performing routine treatment and checking health status routinely make them bore. The aim of this research was to know relations between diabetes mellitus patientâs knowledge about medical treatment and the obedience of routine inspection. This study was cross sectional. Samples taken are 60 respondents with convenience sampling techniques. Knowledge about treatment collect using questionnaires and the level of compliance using study documentation. Statistical tests used correlation spearman rank test to find the values associated with 0.05 Î± level of significance.From total 60 respondents who have knowledge about treatment of diabetes mellitus less criteria 41 respondents (69%). For level of compliance disobedient category are 53 respondents (89%). There is correlation between diabetes mellitus patientâs knowledge about medical treatment and the level of the obedience of routine inspection (p value = 0, 033Â£ 0,05).It can be concluded coefficient correlation is low. So, the order is increase knowledge will increase the obedience of routine inspection.